Sources and Legal Principles of Islamic Inheritance* Dynamics in Indonesia - Abdul Ghofur Anshori (Warmadewa Press, 2022)
Islamic inheritance law is one of the important issues in Islam, and is a pillar between the pillars of law which is fundamentally reflected directly from sacred texts that have been agreed upon for its existence. The resutls show that The results of the research were brought to the formal discussion forum of the National Workshop in 1988. Subsequently, in 1991, the government of the Republic of Indonesia formalized the results of the study into an official regulation under the legal umbrella of Presidential Instruction R.I. No. 1 of 1991 concerning the Dissemination of the Compilation of Islamic Law (KHI) as a result of the Workshop held on February 2 to 5, 1988, can be used by Government Agencies and by the public who need it as a guide in resolving problems in the fields of marriage, inheritance, and endowments. As a written formulation of the provisions of Islamic law in Indonesia, the Compilation of Islamic Law (KHI) is organized into several chapters and articles according to the object of the regulation. Specifically regarding Islamic inheritance, the arrangements are arranged in book II which consists of 6 chapters with 44 articles.